Mass spectrometry in the diagnosis of thyroid disease and in the study of thyroid hormone metabolism. Issue 3 (25th November 2020) - Borsò, Marco; Agretti, Patrizia; Zucchi, Riccardo; Saba, Alessandro
Abstract: The importance of thyroid hormones in the regulation of development, growth, and energy metabolism is well known. Over the last decades, mass spectrometry has been extensively used to investigate thyroid hormone metabolism and to discover and characterize new molecules involved in thyroid hormones production, such as thyrotropin‐releasing hormone. In the earlier period, the quantification methods, usually based on gas chromatography–mass spectrometry, were complicated and time consuming. They were mainly focused on basic research, and were not suitable for clinical diagnostics on a routine basis. The development of the modern mass spectrometers, mainly coupled to liquid chromatography, enabled simpler sample preparation procedures, and the accurate quantification of thyroid hormones, of their precursors, and of their metabolites in biological fluids, tissues, and cells became feasible. Nowadays, molecules of physiological and pathological interest can be assayed also for diagnostic purposes on a routine basis, and mass spectrometry is slowly entering the clinical laboratory. This review takes stock of the advancements in the field of thyroid metabolism that were carried out with mass spectrometry, with special focus on the use of this technique for the quantification of molecules involved in thyroid diseases.